MobileOne : the first 22 months. - Tan, Chester Juan Yee. (2008)
This research study focuses on the company MobileOne Asia Pte Ltd, the second mobile phone service provider in Singapore. Our research aims to find the determinant attributes behind the choice of a consumer’s mobile phone service provider. The top 5 determinant attributes found are competitive rates, current cost of service (monthly bills), best overall value, clear reception and no network system breakdown, all of which M1 received top ratings.